FAKTOR PENGHAMBAT DALAM PELAKSANAAN KONSELING ONLINE BERBASIS TEKS (CHAT) - Haryadi, Rudi; Rahmah, Fauziatin Noor; Khatimah, Khusnul; Irmahwati, Susi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2019)
In the current era of globalization, all technologies are developing rapidly and sophisticated. This is used by all individuals well in helping their work, as well as the world of Guidance and Counseling is greatly helped by the existence of increasingly sophisticated technology. There is no need to worry about distance constraints, because counselors and counselees can still do counseling through the media called online counseling. One of them is through text (chat), this media is very easy to do counselors and counselees because they only communicate by writing or making text. Media chat also helps counselees who have a shy or awkward attitude when meeting directly with a counselor. They only type in a text form to the counselor about the problem. Similar to general counseling, online counseling through media chat also has obstacles in its implementation. This inhibiting factor can be caused by the counselor and his own counselor. The inhibiting factor of the counselor itself is the lack of special knowledge or abilities that the counselor has in communicating through media chat and the lack of skills in writing texts to avoid misunderstandings with the counselee. Likewise counselees such as lack of understanding in using technology also become one of the inhibiting factors. The reason for this article is to find out more about some of the inhibiting factors in counseling through media chat.